2018
DOI: 10.18273/revsal.v50n3-2018007
|View full text |Cite
|
Sign up to set email alerts
|

Genotipificación del Virus de Papiloma Humano en mujeres de la comuna norte de Bucaramanga

Abstract: Introducción: La infección persistente con Virus de Papiloma Humano de alto riesgo es causa necesaria para la aparición de cáncer de cérvix. Objetivo: Caracterizar molecularmente los genotipos circulantes de Virus de Papiloma Humano en población de la zona Norte de Bucaramanga. Métodos: Estudio de corte transversal en mujeres de 35 a 65 años con riesgo ≥3 puntos para desarrollar cáncer de cérvix determinado por una encuesta estandarizada. En una muestra cervico-vaginal por autotoma se realizaron pruebas molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
3
1
1
Order By: Relevance
“…The 22.5% prevalence of HR-HPV found in this study is considered high when compared to some reports in Colombia such as Torrado’s et al [ 17 ] that found 3.9% and Perez’s et al [ 24 ] with 11.5%. However, it is lower when comparing with other Colombian studies, for example, the one of Puerto et al [ 10 ] that reported 42.2%.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The 22.5% prevalence of HR-HPV found in this study is considered high when compared to some reports in Colombia such as Torrado’s et al [ 17 ] that found 3.9% and Perez’s et al [ 24 ] with 11.5%. However, it is lower when comparing with other Colombian studies, for example, the one of Puerto et al [ 10 ] that reported 42.2%.…”
Section: Discussioncontrasting
confidence: 58%
“…This can serve as a baseline for evaluating the impact of vaccination as stated by Garland et al [ 35 ], and as a stimulus for improving education and vaccination coverage. Moreover, this study may be useful for maintaining adherence to screening programs by designing public heath interventions that take ethnic diversity into account [ 17 ]. In addition to contributing to the knowledge of HPV infection and coinfection in women, it helps to reduce the health services gap related to Indigenous peoples in the world [ 34 ] and specifically in this Amazon reserve.…”
Section: Discussionmentioning
confidence: 99%
“…The amplification cycles were as follows: 1 cycle 10 min at 25 °C; 1 cycle at 94 °C for 3 min; 15 cycles of denaturation at 94 °C 30s, alignment 42 °C 30s and elongation 72 °C 30s; 35 cycles of denaturation at 94 °C 30s, alignment 60 °C, elongation 72 °C 30s, 1 cycle at 72 °C for 5 min and finally 5 min 8 ° C. Hybridization was performed in CHIP HPV membranes containing specific probes for HPV-High Risk (HR) and HPV-Low Risk (LR) genotypes. 16 …”
Section: Methodsmentioning
confidence: 99%
“…The amplification cycles were as follows: 1 cycle 10 min at 25 °C; 1 cycle at 94 °C for 3 min; 15 cycles of denaturation at 94 °C 30s, alignment 42 °C 30s and elongation 72 °C 30s; 35 cycles of denaturation at 94 °C 30s, alignment 60 °C, elongation 72 °C 30s, 1 cycle at 72 °C for 5 min and finally 5 min 8 ° C. Hybridization was performed in CHIP HPV membranes containing specific probes for HPV-High Risk (HR) and HPV-Low Risk (LR) genotypes. 16 Statistical Analysis Sociodemographic characteristics were described using absolute and relative frequencies for qualitative variables. For age and body mass index (BMI) variables, the median and interquartile range (IQR) were used because they had no normal distribution.…”
mentioning
confidence: 99%
“…Se obtuvieron muestras de cepillado cervical de mujeres residentes de la zona norte de Bucaramanga, por medio de un dispositivo para auto-toma según el procedimiento y los criterios de inclusión y exclusión descritos previamente (14). Se seleccionaron todas las muestras positivas para VPH (n = 59) que fueron analizadas previamente por amplificación multiplex del gen L1 por PCR, con subsecuente hibridación reversa con la técnica HPV Direct Flow CHIP, hasta el momento de la ejecución del presente estudio.…”
Section: Población De Estudio Y Selección De Muestras Cervicalesunclassified